National Reference Unit Cost of Health‑care Services: International Experiences - Riewpaiboon, Dr. Arthorn (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Costing information is vitally important for public health management. It is applied in relation to priority setting concerning health problems, cost control, health economic evaluation, and health-care financing. When calculating the cost of illness as well as the cost of the health-care program, the cost of the same quantity of utilized services can be different if their unit costs are different. Many countries have attempted to alleviate such difficulties by developing a standard or reference list of the unit cost of health-care services. Aims: This review aimed to explore the situation of the national reference unit cost (NRUC) of health-care services in various countries. Materials and Methods: The study was designed as a systematic review. We searched articles from the PubMed and Google Scholar databases in November 2015 using a combination of keywords, MeSH terms, and other free text terms considered suitable for the purpose. The study only included complete peer-reviewed publications that were reported in the English language. Editorial, reviewed, or methodological articles were excluded. Results: Of the 437 identified citations, seven articles related to the unit cost of medical services studies met the selection criteria. These studies were conducted in Canada, the Netherlands, Australia, Thailand, the Philippine, the United Kingdom, and India. The NRUC has been introduced into economic evaluation analysis or reimbursement. Australia was the first country to publish a standard unit cost study in 1992, while the standard costs list for health economic evaluation in Thailand, which was published in 2014, is the newest available list. The standard unit cost list in England is updated annually and provided to all hospitals. Both top-down and bottom-up costing methodologies were used to validate the accuracy of the results. Conclusion: This first systematic review concerning the NRUC of medical services clearly showed that the current situation, as well as the international methodological guidelines for conducting and reporting the NRUC of health-care services, should be developed as soon as possible.